Political Corruption as Deformities of Truth - Allard-Tremblay, Yann (Les ateliers de l'éthique / The Ethics Forum, 2014)
This paper presents a conception of corruption informed by epistemic democratic theory. I first explain the view of corruption as a disease of the political body. Following this view, we have to consider the type of actions that debase a political entity of its constitutive principal in order to assess corruption. Accordingly, we need to consider what the constitutive principle of democracy is. This is the task I undertake in the second section where I explicate democratic legitimacy. I present democracy as a procedure of social inquiry about what ought to be done that includes epistemic and practical considerations. In the third section, I argue that the problem of corruption for a procedural conception of democracy is that the epistemic value of the procedure is diminished by corrupted agents’ lack of concern for truth. Corruption, according to this view, consists in two deformities of truth: lying and bullshit. These deformities corrupt since they conceal private interests under the guise of a concern for truth. In the fourth section, I discuss the difficulties a procedural account may face in formulating solutions to the problem of corruption.